(untitled) (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
Using the quantitative method to collect data from 400 respondents, the main focus of this study was to establish the nexus between local women’s initiatives and the economic wellbeing of iinhabitants in the study area. Their initiatives in the aspects of involvement in agricultural production, rural education, encouragement of women’s membership in cooperative societies, and socio-economic impact have been specifically examined. The study was sustained on the functionalist perspective. The research design was a survey while the multi-stage sampling technique was adopted. The data obtained were analyzed using descriptive statistics and the Pearson Product Moment Correlation Co-efficient. Findings revealed that a significant relationship exists between involvement in agricultural production, involvement in rural education, and promotion of membership in cooperative societies and the socio economic wellbeing of inhabitants. The study concluded that local women’s initiatives are essential strategies for the enhancement of the socio economic well- being of inhabitants of rural communities. The policy implication is that women should be encouraged in their local initiatives, especially in agricultural production, through extension education and accessibility to loans, in order to arrest the relative stagnation of agriculture and reduce rural poverty.